한국인 유방암 조직에서의 인테그린의 발현 - 김홍(Hong Kim); 정용식(Yong Sik Jung); 김혜진(Hye Jin Kim); 임현이(Hyun Hee Im); 이진우(Jin Woo Lee); 변종석(Jong Seok Byun); 김명욱(Myung Wook Kim); 박희붕(Hee Boong Park) (Annals of surgical treatment and research, 2003)
KCI Citation Count: 0